MODELLING AND AUTOMATION OF PROCESS OF WATER PURIFICATION BY MAGNETIC FILTER - Safonyk, Andrii (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2016)
The model problem of type "convection-mass-transfer" is solved for the process of cleaning of water mediums in the grainy magnetized filter material. The mathematical analysis of parameters and model of process of the magnetic sediment of admixtures was done. The system of automation of process of permanent water purification from magnetic admixtures was worked out.